Effect of tungsten off-axis accumulation on neutral beam deposition in JET rotating plasmas. (25th February 2015) - Koskela, T; Romanelli, M; Belo, P; Asunta, O; Sipilä, S; O'Mullane, M; Giacomelli, L; Conroy, S; Mantica, P; Valisa, M; Angioni, C; Kurki-Suonio, T
Abstract: Evidence for low field side accumulation of tungsten is often observed in bolometry and soft x-ray emissivities of highly rotating JET ITER-like wall (ILW) plasmas. Poloidal variation of the density of high-Z impurities, such as tungsten, in the core of NBI heated plasmas is expected from neoclassical theory due to charge displacement and parallel electric field generated by the centrifugal force. We calculate the poloidally asymmetric distribution of tungsten using fluid equations and a 1D transport simulation with the JETTO/SANCO code. Peaking of tungsten on the outboard side of the plasma is found and verified with soft x-ray and bolometry measurements. We then study the effect of a poloidally asymmetric tungsten distribution on the distribution of the NBI heat source by simulations with the Monte Carlo code ASCOT. The simulations show that the poloidally asymmetric tungsten profile redistributes the fast NBI ions radially through shifting their ionization profile and poloidally through enhanced pitch-angle scattering at high energy. The amplitude of the redistribution is in the order of 10% for the highest n W / n e ratios of ∼10 −4 measured in recent JET H-mode plasmas. As a result of the scattering of the beam particles, the core heat deposition is changed less than 10%, which does not have a significant impact to the performance of JET plasmas. The modelling is in qualitative agreement with measurements by the vertical neutron camera that sees a broadening in the 2.5 MeV neutron profile when tungsten peaks on the outboard side of the plasma.